Implementasi Prinsip Transparansi dan Akuntabilitas dalam Pengelolaan Anggaran Belanja Infrastruktur di Dinas PUTR Kota Pematangsiantar - Muhammad Hizry Andriyantama; Fauzi Arif Lubis; Nurlaila (Jurnal Riset Akuntansi, 2025)
This study analyzes the implementation of transparency and accountability in the management of the infrastructure expenditure budget at the Public Works and Spatial Planning Office (PUTR) of Pematangsiantar City. Using a qualitative approach of case studies, data is collected through interviews, field observations, and document analysis. The results of the study show that the PUTR Office has implemented a number of transparency mechanisms, such as the Information and Documentation Management Officer (PPID), official websites, and project information boards. In addition, a layered accountability system involves both internal and external stakeholders. However, a gap was found between formal and substantive transparency: detailed budget documents, such as Budget Implementation Documents (DPAs), Budget Work Plans (RKAs), and Budget Realization Reports (LRAs), were not proactively published through the website, but were only available through reactive PPID procedures. The study also highlights that strong vertical accountability to regulatory agencies does not automatically result in horizontal transparency to the public. These findings contribute to the good governance literature by emphasizing that transparency and accountability do not always go hand in hand in practice, so a more integrative policy strategy is needed to ensure information disclosure as well as public accountability in the management of regional infrastructure budgets.